Satellite tracking identifies important foraging areas for loggerhead turtles frequenting the Adriatic Sea, Central Mediterranean - MENCACCI, RESI; AIUDI, LAURA; ANGELINI, VALERIA; CASALE, PAOLO; CERRITELLI, GIULIA; LOMBARDI MORAES, KAMYLA; PARI, SAURO; Luschi, Paolo (Mediterranean Marine Science, 2023)
The Adriatic Sea is one of the main foraging areas for marine turtles of the Mediterranean Sea, but the specific high-use sites are poorly known, due to the scarceness of satellite tracking data available for juvenile turtles frequenting the area. In the present study, we tracked 8 juvenile and adult loggerhead turtles (Caretta caretta) that were released along the north-western Adriatic coast after a rehabilitation period having been equipped with Argos-linked satellite transmitters. Tracked turtles displayed quite variable movement patterns, but mostly remained in the north-western Adriatic, especially during the summer months. A marked preference for specific coastal sites was revealed in many turtles, that actively moved towards these specific locations when released south of it or having spent the winter away. Pooling these data with those obtained in previous studies on a further 10 turtles, we highlighted the presence of two main high-use areas, north and south of the Po River delta, where future conservation actions may then be focused.